Commercial shrimp landings of two penaeid shrimps in the main markets of Basrah Province, Iraq - Abbas, Ashwaq T.; Ghazi, Abdul-Hussein H. (Mesopotamian Journal of Marine Sciences, 2021)
Two penaeid shrimp species were found in the main fish markets of Basrah Province, Penaeus semisulcatus and Metapenaeus affinis. The quantities of the two species were recorded, the highest landings of P. semisulcatus in Al-Ashar market was 396 +26 kg during September, and the lowest during December (159 +16 kg). In Basrah market, the highest landings was observed in July (410 +32 kg), and the lowest was 200 +22 kg in January. As for M. affinis, the highest landings was 397 +55 kg in July at Al-Ashar market, and the lowest rate in December, which reached 205 +19 kg. In Al-Basrah market, the highest rate of landings was 597 +68 kg in July, and the lowest rate (298 +48 kg) in November. The highest average monthly weight of P. semisulcatus was 80 +7 g during January and the lowest average was 40 +6 g in April. For M. affinis the highest average weight was 25 +5 g. in December and the lowest (12 +6 g.) in May. The highest annual landings of P. semisulcatus in Al-Ashar market was 15.5 tones and in Al-Basrah market was 18 tones. While the highest annual rate of landings of M. affinis in Al-Ashar market was 12.7 tones and in Al-Basrah market 25.8 tones.